KEDUDUKAN DAN KEKUATAN PEMBUKTIAN DEEPFAKE DALAM PROSES PERSIDANGAN - Soffyan Angga Fahlani; Eko Taufikur Rahman; Muhammad Azianor Ilmy; Arisandy Mursalin (Al-Adl : Jurnal Hukum, 2026)
Technological advancement has extended to the rapid development of artificial intelligence (AI), which has the capacity to facilitate human work and activities. One notable technological innovation is AI-based deepfake technology, which is capable of altering or generating images, videos, and audio with a high degree of resemblance to their original counterparts. While deepfakes offer benefits in creative and industrial domains, they also pose significant legal challenges, particularly with respect to misuse for cybercrime, the dissemination of disinformation, defamation, and violations of privacy. This study addresses the legal status of deepfakes within the classification of legal objects or subjects under the prevailing legal framework in Indonesia, as well as their evidentiary value under criminal procedural law and the Electronic Information and Transactions Law. This research employs a normative juridical method with statutory and conceptual approaches. Data collection is based on primary legal materials, particularly Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 on Electronic Information and Transactions (UU ITE), as well as secondary legal materials derived from relevant legal scholarship. The findings indicate that deepfakes may be classified as electronic information and/or electronic documents that possess legal standing as objects of law within the UU ITE framework. Furthermore, deepfakes may serve as admissible evidence in criminal proceedings, provided that the requirements of authentication, integrity, and relevance are satisfied. Through an expansive interpretative approach, deepfakes may also be construed as circumstantial evidence. Nevertheless, the assessment of their evidentiary validity necessitates the support of digital forensic analysis to verify the authenticity and integrity of electronic content. Accordingly, regulatory reinforcement and more comprehensive oversight mechanisms governing the use of deepfake technology are essential to prevent misuse that may cause harm to individuals and society at large.